Conventional and novel anti-seizure medications reveal a particular role for GABAA in a North Sea progressive myoclonus Epilepsy Drosophila model. - Polet, S.S.; de Koning, T.J.; Lambrechts, R.A.; Tijssen, M.A.J.; Sibon, O.C.M.; Gorter, J.A. (Epilepsy research, 2024)
North Sea Progressive Myoclonus Epilepsy (NS-PME) is a rare genetic disorder characterized by ataxia, myoclonus and seizures with a progressive course. Although the cause of NS-PME is known, namely a homozygous mutation in the GOSR2 gene (c.430 G>T; p. Gly144Trp), sufficient treatment is lacking. Despite combinations of on average 3-5 anti-seizure medications (ASMs), debilitating myoclonus and seizures persist. Here we aimed to gain insight into the most effective anti-convulsive target in NS-PME by evaluating the individual effects of ASMs in a NS-PME Drosophila model. A previously generated Drosophila model for NS-PME was used displaying progressive heat-sensitive seizures. We used this model to test 1. a first-generation ASM (sodium barbital), 2. common ASMs used in NS-PME (clonazepam, valproic acid, levetiracetam, ethosuximide) and 3. a novel third-generation ASM (ganaxolone) with similar mode of action to sodium barbital. Compounds were administered by adding them to the food in a range of concentrations. After 7 days of treatment, the percentage of heat-induced seizures was determined and compared to non-treated but affected controls. As previously reported in the NS-PME Drosophila model, sodium barbital resulted in significant seizure suppression, with increasing effect at higher dosages. Of the commonly prescribed ASMs, clonazepam and ethosuximide resulted in significant seizure suppression, whereas both valproic acid and levetiracetam did not show any changes in seizures. Interestingly, ganaxolone did result in seizure suppression as well. Of the six drugs tested, three of the four that resulted in seizure suppression (sodium barbital, clonazepam, ganaxolone) are primary known for their direct effect on GABAA receptors. This suggests that GABAA could be a potentially important target in the treatment of NS-PME. Consequently, these findings add rationale to the exploration of the clinical effect of ganaxolone in NS-PME and other progressive myoclonus epilepsies.